A-06 Current Norms May Overestimate Rates of Neurocognitive Impairment among American Indian and Alaskan Native Adults. (28th August 2020) - Savin, M; Summers, A; Crook, C; Aghvinian, M; Byrd, D; Armenta, R; Franklin, D; Marcotte, T; Rivera Mindt, M
Abstract: Objective: Currently available normative data subsume American Indian and Alaskan Native (AI/AN) populations within the non-Latinx white (NLW) ethnoracial group. The classification accuracy of such norms among AI/AN remains unknown. This cross-sectional study aims to identify whether disparities exist in the rates of neurocognitive impairment (NCI) between AI/AN and NLW adults. < br> Method: Two hundred community-dwelling adults (50% NLW; 50% Male; M Age = 42 ± 14 years; M Education = 13 ± 3 years) completed comprehensive neurocognitive, quality of education (Wide Range Achievement Test- 4 [WRAT-4]), neuromedical, urine toxicology, and psychiatric/substance use evaluations. Average T-scores were calculated using widely used demographically corrected (age, gender, education) NLW norms to identify NCI (> 1 SD; e.g., Heaton et al., 2004; Heaton & Marcotte, 2000). A comorbid condition propensity score (CCPS) identified the probability to which comorbid conditions (e.g., Heaton et al., 2010) informed ethnoracial identity; Results: After adjusting for WRAT-4 and CCPS, the results of a logistic regression analysis demonstrated a significant ethnoracial disparity in risk for NCI (X2(3) = 13.88, p<.01, R2 = .07), such that the AI/AN group was at 2.52 times higher odds (32.3% vs. 16.0, CI: 1.15–5.46, p = .01, Cohen's d = .51) for NCI in comparison to the NLW group; Conclusions: Published norms for NLW adults may overestimate impairment in AI/AN adults. Thus, population-specific normative data are needed to clarify the classification accuracy of neurocognitive impairment and possible disparities in neurocognitive disorders (e.g., HIV-associated neurocognitive disorders) among AI/AN adults. Future work should replicate these findings among other diverse populations (e.g., Caribbean, Middle Eastern) lacking population-specific normative data.876199.